Coil Inductance Design for Low Power Hybrid Wireless Power Transfer. Issue 1 (March 2020) - Kurniawan, T A; Gumilang, R B; Wibisono, G
Abstract: This paper presents a coil inductance design for low power hybrid wireless power transfer (WPT). The proposed coil inductance design of transmitter and receiver circuits of 7.1 μH are designed using handmade copper wire structure. Several coils with the variations of wire diameters, coil loop radius, and numbers of loops are proposed to find optimum structure in the low power hybrid WPT. The optimum coil structure is obtained at wire diameter of 0.5 mm, 2.25-inch coil loop radius and 1 MHz operation frequency. The measured transceiver coil design has exhibited peak power transfer efficiency (PTE) of 33.1% at 1 cm distance between Tx and Rx. Therefore, the proposed coil design is applicable to low power hybrid wireless power transfer circuits.